The influence of antioxidant postharvest treatment on content of biologically active substances during storage of cucumbers - Прісс, Олеся Петрівна; Присс, Олеся Петровна; Priss, Olesia; Легеза, Дар'я Георгіївна; Легеза, Дарья Георгиевна; Legeza, Daria; Жукова, Валентина Федорівна; Жукова, Валентина Федоровна; Zhukova, Valentyna; Іванова, Ірина Євгенівна; Иванова, Ирина Евгеньевна; Ivanova, Iryna (My University, 2017)
EN: The influence of heat treatment with antioxidant compositions on the content of biologically active substances during storage of cucumbers is investigated. It was found that the use of the proposed treatment inhibits the activity of ascorbate oxidase by 15–18%, which allows to slow down the decomposition of ascorbic acid by 1.5 times. The content of ascorbic acid in the experimental fruit after storage for 28 days is 1.4 times higher than in the control after 21 days of storage. It was found that in the cucumbers 11–14 sm long, the synthesis of polyphenols continued in the period of storage. The intensity of accumulation of phenolic substances proved to be different in the treated and control groups. It was shown that thermal treatment with antioxidants slowed the growth rate of total polyphenols by 20% relative to control, indicating inhibition of maturation processes. It was revealed that the activity o polyphenol oxidase during the storage of treated fruits was slowing down. It has been established that the application of said treatment substantially inhibits the degradation of chlorophylls. Rapid loss of chlorophyll caused yellowing and loss of consumer properties in the control groups after 2 weeks of storage. In processed cucumbers only 21 days of storage revealed a decrease in the concentration of chlorophyll in relation to the moment of laying. At day 28 the amount of chlorophylls in the experimental fruit is at the same level as in the control after a week of storage. It has been found that the use of the proposed treatment slows the degradation of carotenoids. The quantity of carotenoids in experimental cucumbers at the end of storage is 21–23% higher than in the control ones. The compensatory function of ascorbic acid, carotenoids and phenolic substances during storage of cucumber fruits is proved. UK: Досліджено вплив післязбиральної обробки антиоксидантними композиціями на вміст біологічно активних речовин під час зберігання огірків. Виявлено, що використання запропонованої обробки гальмує на 15–18% активність аскорбатоксидази, що дозволяє в 1,5 рази сповільнити розпад аскорбінової кислоти. Вміст аскорбінової кислоти в дослідних плодах після зберігання протягом 28 діб в 1,4 рази вищий, ніж в контрольних після 21 доби зберігання. Показано, що післязбиральна обробка антиоксидантами сповільнює темпи зростання поліфенолів на 20% відносно контролю, що свідчить про інгібування процесів дозрівання. Встановлено, що застосування зазначеної обробки істотно інгібує деградацію хлорофілів. В оброблених огірках лише на 21 добу зберігання виявлено зниження концентрації хлорофілів по відношенню до моменту закладання. На 28 добу сума хлорофілів в дослідних плодах знаходиться на тому ж рівні, що і в контрольних через тиждень зберігання. Виявлено, що використання запропонованої обробки сповільнює деградацію каротиноїдів. Кількість каротиноїдів у дослідних огірках на кінець зберігання на 21–23% більша, ніж в контрольних. Доведено компенсаторну функцію аскорбінової кислоти, каротиноїдів і фенольних речовин під час зберігання плодів огірка.
Вплив післязбиральної обробки антиоксидантами на вміст біологічно активних речовин впродовж зберігання огірків
Keywords: storage of cucumbers; phenolic substances; ascorbic acid; carotenoids; chlorophylls; polyphenol; ascorbate oxidase; зберігання огірків; фенольні речовини; аскорбінова кислота; каротиноїди; хлорофіли; поліфенолоксидаза; аскорбатоксидаза